Reconstruction and analysis of the aberrant lncRNA–miRNA–mRNA network in systemic lupus erythematosus. (April 2020) - Xu, H; Chen, W; Zheng, F; Tang, D; Liu, D; Wang, G; Xu, Y; Yin, L; Zhang, X; Dai, Y
Objective: A new perspective of determining the pathophysiology of systemic lupus erythematosus (SLE) development is required. The current study explores the aberrant expression of long non-coding RNAs (lncRNA), microRNA (miRNA) and mRNA. The study further constructs and analyses the lncRNA–miRNA–mRNA network to elucidate their gene regulation roles in SLE. Method: We extracted mRNA, lncRNA and miRNA from the whole venous blood of 20 SLE patients and 20 normal control (NC) healthy individuals. A lncRNA–mRNA–miRNA network in SLE was constructed using a bioinformatics approach. Subsequently, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses were performed using the Cytoscape plug-in BinGo, the DAVID database and Cytoscape software to explore the function of mRNAs in this network. Result: A total of 855 mRNA, 7311 lncRNA and 134 miRNA with differentially expressed profiles were identified. Meanwhile, we established a competing endogenous RNA (ceRNA) subnetwork composed of 52 differentially expressed lncRNAs (DElncRNAs), seven differentially expressed miRNAs and 10 differentially expressed mRNAs. We extracted the subnetwork from the ceRNA network and found that three novel miRNAs were key: hsa-miR-145, hsa-miR-17 and hsa-miR-143. We also deduced that the DElncRNAs MIAT and NEAT1 might play crucial roles in the pathogenesis of SLE. The results were verified by bioinformatics analysis. Conclusion: Our results provide a novel perspective for studying lncRNA-related and miRNA-related ceRNA networks in SLE.